Торпедирование культурного наследия Арцаха на Азербайджанских медиа площадках - Овсепян, Рубен (Институт языкознания РАН)
После окончания 44-дневной второй Арцахкой войны азербайджанская сторона начала вести агрессивную пропаганду, направленную на присвоение историко-культурного наследия Арцаха, на его искажение и особенно на антиармянскую пропаганду. Для анализа методов пропаганды важен мониторинг азербайджанских средств массовой информации и страниц в социальных сетях с целью сбора данных о пропаганде, направленной на присвоение культурного наследия Арцаха. After the end of the 44-day war in 2020, the Azerbaijani side began an intensive propaganda aimed at appropriation of the cultural and historical heritage of Artsakh, its distortion, and, specifically, anti-Armenian propaganda. To understand the level of propaganda of the Azerbaijani side, it is especially important to monitor different media resources and Azerbaijani social pages. All this gives a huge amount of information about the methods of propaganda which is aimed at appropriating the cultural heritage of Artsakh
Keywords: Наследие Арцаха; Культура; История; Пресса